Stress distribution in pediatric zirconia crowns depending on different tooth preparation and cement type: a finite element analysis - Sang-Yeop Chung; Hyeonjong Lee; Yong Kwon Chae; Yun Sun Jung; Su-Sung Jo; Ko Eun Lee; Sung Chul Choi; Ok Hyung Nam (BMC Oral Health, 2022)
Abstract Background In clinical settings, tooth preparation for prefabricated zirconia crowns (PZCs) in the primary dentition varies widely. However, knowledge about the biomechanical behavior of PZCs in various clinical settings is limited. This study was conducted to evaluate the biomechanical behavior of PZCs in different clinical settings using 3-dimensional finite element analysis. Methods 3-dimensional models of the PZC, cement, and tooth with six different conditions were simulated in primary molar teeth, incorporating cement thickness (100, 500, and 1000 μm) and cement type (resin-modified glass ionomer cement and resin cement). A total of 200 N of occlusal force was applied to the models, both vertically and obliquely as representative cases. A general linear model univariate analysis with partial eta-squared (ηp2) was performed to evaluate the relative effects of the variables. Results The overall stress of tooth was increased as the cement space increases under oblique loading. The von Mises stress values of the resin cements were significantly higher than those of the resin-modified glass ionomer cements for all cement thicknesses (p < .05). The effect size of the cement type (ηp 2 = .519) was more dominant than the cement thickness (ηp 2 = .132) in the cement layer. Conclusions Within the limits of this study, cement type has a greater influence on the biomechanical behavior of PZCs than cement thickness.